Sleep and Sleep Disturbance in Children: Reliability and Validity of the Dutch Version of the Child Sleep Habits Questionnaire - Waumans, Ruth C. (Associated Professional Sleep Societies, LLC, 2010)
STUDY OBJECTIVES: The Child Sleep Habits Questionnaire (CSHQ) was developed in the US for measuring medical and behavioral sleep disorders in school-aged children. This study was conducted to assess the reliability and structural validity of the Dutch version of the CSHQ. DESIGN: Population-based study SETTING: Questionnaires (n = 2385) were distributed to children in primary schools and daycare centers to be completed by the parent/guardian. An identical second questionnaire was distributed for test-retest and interobserver reliability, which were assessed using intraclass correlation, and compared with published data. Internal consistency was assessed by Cronbach α (per subscale). Validity was analyzed by confirmatory and exploratory factor analysis. PARTICIPANTS: School-aged children. INTERVENTIONS: None. MEASUREMENTS & RESULTS: The questionnaire was returned by 1502 (63%) parents, 47% returned the questionnaire for test-retest, and 32% for interobserver reliability. Test-retest reliability was moderate to good, ranging from 0.47 to 0.93. Interobserver reliability was moderate to good, ranging from 0.53 to 0.87, with the exception of Sleep duration. Cronbach α ranged from 0.47 to 0.68. In confirmatory factor analysis the domain structure of the original American CSHQ could not be confirmed. Exploratory factor analysis suggested a 4-factor structure rather than the original 8 domains. CONCLUSIONS: The CSHQ seems to have an adequate reliability and moderate internal consistency in a Dutch population with different sociocultural characteristics than the US population in which it was devised. Factor analysis suggests that translation, cultural background, or subscales of the original instrument may affect the performance of the CSHQ. CITATION: Waumans RC; Terwee CB; Van den Berg G; Knol DL; Van Litsenburg RRL; Gemke RJBJ. Sleep and sleep disturbance in children: reliability and validity of the Dutch version of the Child Sleep Habits Questionnaire. SLEEP 2010;33(6):841-845.